2013
DOI: 10.1152/ajprenal.00344.2013
|View full text |Cite
|
Sign up to set email alerts
|

Complement 3 activates the renal renin-angiotensin system by induction of epithelial-to-mesenchymal transition of the nephrotubulus in mice

Abstract: We have demonstrated that mesenchymal cells from spontaneously hypertensive rats genetically express complement 3 (C3). Mature tubular epithelial cells can undergo epithelial-to-mesenchymal transition (EMT) that is linked to the pathogenesis of renal fibrosis and injury. In this study, we investigated the contribution of C3 in EMT and in the renal renin-angiotensin (RA) systems associated with hypertension. C3a induced EMT in mouse TCMK-1 epithelial cells, which displayed increased expression of renin and Krüp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 41 publications
5
64
1
Order By: Relevance
“…Emerging evidence suggests that intragraft complement activation contributes to this progressive kidney injury (108). C3 is implicated in the activation of the renin-angiotensin system and the epithelial-to-mesenchymal transition (109,110). Together with observations that absence/blockade of C5/C5aR (but not blocking MAC formation) limited kidney fibrosis in several animal models (111,112), the data suggest that kidney-derived complement participates in fibrosis of native and transplanted kidneys (Figure 7).…”
Section: Kidney-derived Complement and Diseasementioning
confidence: 85%
“…Emerging evidence suggests that intragraft complement activation contributes to this progressive kidney injury (108). C3 is implicated in the activation of the renin-angiotensin system and the epithelial-to-mesenchymal transition (109,110). Together with observations that absence/blockade of C5/C5aR (but not blocking MAC formation) limited kidney fibrosis in several animal models (111,112), the data suggest that kidney-derived complement participates in fibrosis of native and transplanted kidneys (Figure 7).…”
Section: Kidney-derived Complement and Diseasementioning
confidence: 85%
“…A protective effect was also observed when UUO mice were treated with a C5aR antagonist. In a more recent study of UUO in C3 deficient mice there was a significant reduction in interstitial fibrosis and tubular atrophy in the absence of complement activation [47] . It is clear from the above animal studies that activation of C3 and C5 contribute to the development of progressive renal fibrosis during experimental obstructive nephropathy, however, the mechanism by which this occurs remains largely uncharacterised.…”
Section: Complement Activation In Clinical Proteinuric Diseasementioning
confidence: 87%
“…Complement participates in EMT in murine models of renal injury and fibrosis (62,80,81). We showed that complement activation inside tumors not only increases tumor growth but also enhances metastasis by promoting EMT in cancer cells.…”
Section: Complement Activation In Epithelial-mesenchymal Transitionmentioning
confidence: 91%
“…(59) and T cells (22), and increases cell proliferation in endothelial (60) and colon cancer cell lines (61). Activation of C3aR plays an important role in guiding collective cell migration (26) and epithelial-mesenchymal transition (62,63), both important mechanisms in metastasis. In a sublytic density, MAC accumulation on the cell membrane promotes cell proliferation (64) and differentiation, inhibits apoptosis (10,65), and protects cells against complement-mediated lysis (66).…”
Section: Complement and Cancermentioning
confidence: 99%